SMART HOME (INNOVATION) SMART CITY SYSTEM - Samsuriah (P3M STMIK Profesional Makassar, 2016)
Smart Home is an integration between the technologies and services that are implemented on a home. This study aims to improve the security, safety, comfort and energy savings. This research uses descriptive method. Data were analyzed using the basic theories of smart home, which uses server. The concept of smart home is not the technology of the future, this concept has been developed at this time and have a direct impact on the lifestyle of people in it. The results showed that a person who is outside the home can interact and controlling of all devices in the home by simply using mobile devices such as smartphones.